2013
DOI: 10.4049/jimmunol.1201190
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for C5aR Signaling in the Optimal Induction of a Malaria-Specific CD4+ T Cell Response by a Whole-Killed Blood-Stage Vaccine

Abstract: The protective immunity induced by the whole-killed parasite vaccine against malarial blood-stage infection is dependent on the CD4+ T cell response. However, the mechanism underlying this robust CD4+ T cell response elicited by the whole-killed parasite vaccine is still largely unknown. In this study, we observe that immunization with Plasmodium yoelii–parasitized RBC lysate activates complement C5 and generates C5a. However, the protective efficacy against P. yoelii 17XL challenge is considerably reduced, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 47 publications
(54 reference statements)
0
31
0
2
Order By: Relevance
“…For serum transfer, naive BALB/c mice were injected i.v. on days Ϫ1, 0, and 1 with 0.2 ml of naive mouse serum, ITV-immunized wild-type (WT) serum, or PD-1 Ϫ/Ϫ mouse serum collected 21 days after the last CQ injection, as described previously (15). The mice were challenged with 2.5 ϫ 10 4 PyiRBCs on day 0, and parasitemia and the survival rate were determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For serum transfer, naive BALB/c mice were injected i.v. on days Ϫ1, 0, and 1 with 0.2 ml of naive mouse serum, ITV-immunized wild-type (WT) serum, or PD-1 Ϫ/Ϫ mouse serum collected 21 days after the last CQ injection, as described previously (15). The mice were challenged with 2.5 ϫ 10 4 PyiRBCs on day 0, and parasitemia and the survival rate were determined.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperimmune sera were collected from the ITVimmunized WT mice that had recovered from the P. yoelii 17XL infection. The malaria-specific total IgG, IgG1, and IgG2a in the serum were detected as previously described (15,17). Briefly, P. yoelii 17XL-infected mouse blood was collected, lysed with 0.01% saponin (Sigma-Aldrich) at 37°C for 20 min, and sonicated in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the stimulatory role of activated DCs in IFN-g production by naive CD4 + T cells in murine malaria models (40,(53)(54)(55), as well as the demonstration that APCs from KO mice are hyperresponsive to LPS and exhibit increased priming capabilities (36), two possible mechanisms may account for the differing IFN-g response derived from CD4 + T cells in the two groups of mice: one is the direct influence of MKP5 deficiency on T cell activity, the other is the indirect modulation on DC function. By using an in vitro coculture approach to mimic the initial interaction between the parasite-activated DCs and naive CD4 + T cells, we found that splenic DCs from infected KO mice incubated with CD4 + T cells could produce higher levels of IFN-g, whereas the different sources of CD4 + T cells did not affect the response levels, suggesting that the ability of DCs to induce CD4 + T cell IFN-g production is significantly enhanced in the absence of MKP5 early after P. yoelii 17XL infection.…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, além desse papel protetor, C5 também é responsável por aumentar o grau de lesão em diferentes modelos experimentais (Pritchard et al, 2007). Devido a capacidade de C5a estimular e atrair diversos tipos celulares para o sítio de inflamação (Liu et al, 2013;Mashruwala et al, 2011;Mollnes et al, 2002;Moulton et al, 2007;Snyderman et al, 1971;Ward, Zvaifler, 1971) …”
Section: Discussionunclassified
“…Camundongos C5 deficientes possuem menor atividade de linfócitos T CD4 + , macrófagos e células dendríticas (Liu et al, 2013;Mashruwala et al, 2011;Moulton et al, 2007). Macrófagos e células dendríticas desses animais produzem menores quantidades de IL-12p70 que as células de animais C5 normais.…”
Section: Figura 8 -Receptores De C5aunclassified